The Impact of the Extension on Anti-dumping Measures on Imports: A Study on Steel Products - Lubis, Shameira Rizkia (Gorontalo State University, 2025)
This study conducts research related to the impact of implementing trade policies in the form of anti-dumping measures, which influence changes in import patterns from targeted countries. Analysis results using the difference-in-difference (DID) method, which compares the volume of imports from targeted and non-targeted countries in the period before and after the implementation of anti-dumping measures, show that the extension of anti-dumping measures has a significant effect on reducing imports from countries targeted by such measures. This research will provide new insight into the impact analysis of the implementation of anti-dumping measures for steel products in Indonesia, with observations that have experienced an extension of the measures.